(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The article is dedicated to the elucidation of feasibility of application in the RA of the theoretical models of regional economic policy by leading countries and, in this context, the efficiency of on-going programs in the country.